Perkembangan Jiwa Beragama Islam pada Siswa SD Kelas V - Ramadan Lubis; Siti Aminah; Nur Laily Fitri; Vita Shahnaz Maharani Rangkuti; Nur Aqilah Pohan; Zakiyah Andiny Sihombing (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2024)
This research aims to examine the development of the Islamic religious spirit in grade 5 MIN 3 elementary school students in Medan City in terms of theory, the factors that influence it, and efforts to develop it. The author uses a qualitative approach with a literature study method. The author describes the development of the Islamic religious spirit in grade 5 MIN 3 elementary school students in Medan City based on three domains, namely: the cognitive domain, the affective domain, and the psychomotor domain. The author also presents several learning methods that can be used by Islamic religious education teachers to develop these three domains. The results of the research show that the development of the Islamic spirit in students at SD 5 MIN 3 in Medan City is influenced by various factors, including: nature, environment, education and experience. The development of the Islamic spirit in grade 5 MIN 3 elementary school students in Medan City can be improved by using effective, interesting and fun learning methods.